The mine locomotive wireless network strategy based on successive interference cancellation with dynamic power control. (May 2017) - Shi, Lei; Gao, Yu; Wei, Zhenchun; Ding, Xu; Shi, Yi
Mine locomotives are widely used in mining industry for transporting. Usually, these locomotives need to move along the tunnels and communicate with access points which are equipped on the side of these tunnels. It is important to maintain high-quality communication services due to the unsafe underground working environment. In this article, we design the mine locomotive wireless network strategy based on successive interference cancellation with dynamical power control. We first divide the whole schedule time into time segments and build the problem model in each time segment. To maximize throughput for each time segment, we formulate a linear programming problem based on certain features of successive interference cancellation decoding order. However, this problem has lots of constraints which makes it hard to solve in polynomial time. Then, we propose a concept of the maximum successive interference cancellation set to reduce the problem size. Based on this concept, we propose a polynomial complexity algorithm named max-SIC-set algorithm. Simulation results show that our algorithm can increase throughput significantly compared with the algorithm using successive interference cancellation only (no power control) and with the algorithm without using successive interference cancellation and power control.